2014
DOI: 10.1371/journal.pone.0105059
|View full text |Cite
|
Sign up to set email alerts
|

Host Density and Competency Determine the Effects of Host Diversity on Trematode Parasite Infection

Abstract: Variation in host species composition can dramatically alter parasite transmission in natural communities. Whether diverse host communities dilute or amplify parasite transmission is thought to depend critically on species traits, particularly on how hosts affect each other’s densities, and their relative competency as hosts. Here we studied a community of potential hosts and/or decoys (i.e. non-competent hosts) for two trematode parasite species, Echinostoma trivolvis and Ribeiroia ondatrae, which commonly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 72 publications
(80 reference statements)
0
22
1
1
Order By: Relevance
“…Nevertheless, other recent studies have similarly reported no effect (Raffel et al, 2010;Marino & Werner, 2013) or even a positive effect (Johnson et al, 2013;Wojdak et al, 2014) of density on larval amphibian trematode infection at the mesocosm scale. Our sample sizes for dissection were limited and necessarily did not include animals that died during the experiments, as dead tadpoles are typically not visible in the large mesocosms and rapidly degrade.…”
Section: Discussionmentioning
confidence: 82%
“…Nevertheless, other recent studies have similarly reported no effect (Raffel et al, 2010;Marino & Werner, 2013) or even a positive effect (Johnson et al, 2013;Wojdak et al, 2014) of density on larval amphibian trematode infection at the mesocosm scale. Our sample sizes for dissection were limited and necessarily did not include animals that died during the experiments, as dead tadpoles are typically not visible in the large mesocosms and rapidly degrade.…”
Section: Discussionmentioning
confidence: 82%
“…; Wojdak et al . ). However, these designs still obscure the dynamical feedbacks and interactions described above.…”
Section: Discussionmentioning
confidence: 97%
“…; Wojdak et al . ), we allow our host species to dynamically interact and mechanistically influence each other's densities via these traits. Then, we explore a range of realistic outcomes in our community module (three case studies) by measuring intraspecific variation in the traits of our focal host ( sensu Bolnick et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intuitively, host regulation might matter more when predation (Rohr et al., ) or competition (Strauss et al., ) depresses focal host densities more strongly. Encounter reduction appears stronger when diluters remove parasites more rapidly and strongly resist infection (Venesky, Liu, Sauer, & Rohr, ; but see Wojdak, Edman, Wyderko, Zemmer, & Belden, ). Yet, intraspecific variation in susceptibility among focal hosts may counter either dilution mechanism by fuelling uncontrollably large or inconsequentially small epidemics (Strauss et al., ).…”
Section: Introductionmentioning
confidence: 99%